Printing of passive RFID tag antennas on flexible substrates for long read distance applications: Materials and techniques - Mohd Nizar Hamidon; Tark D. Farnana; Intan H. Hasan; Aduwati Sali; Maryam Md. Isa (Journal of Science: Advanced Materials and Devices)
Radio frequency identification (RFID) is an emerging technology that has a crucial role in many areas. To be suitable for these applications, RFID tags must be flexible, which presents greater manufacturing challenges. Printing as an additive manufacturing method is preferred over subtractive processes due to its efficient use of materials and environmental friendliness. This review presents key properties of the printed patterns, namely electrical conductivity, layer thickness, and surface morphology. It links them to the reading distance between the RFID tag and the reader. The types of conductive inks and their role in achieving a long-read distance of flexible antennas are also discussed. The properties of flexible substrates linked to the printing process are also presented. These substrates were classified into paper, polymer, and textiles. This article considers two laboratory-scale printing techniques commonly used in research: inkjet and screen printing. The printing parameters of these printing techniques that affect the printing quality are covered. Furthermore, electroless plating is presented as a metallization process or a complementary method to other printing techniques.